VARIASI BAHASA DAN KELAS SOSIAL - Rizka Hayati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Language is a tool used to communicate and interact in society. Apart from these main functions, the use of language can also reflect the social class of the language user. The variety of language used by a speaker in society in communication can take various forms, depending on situation and condition that accompany it. One of the things that affect language variations in social class. Researchers used observations in data collection. The data analysis technique uses qualitative descriptive, which qualitatively describes linguistic phenomena found in society. The results obtained after conducting the analysis tare that there are several variations in the language used for reasons of social class.